Pengaruh Progressive Muscle Relaxation (PMR) terhadap Penurunan Tekanan Darah pada Penderita Hipertensi di Wilayah Kerja Puskesmas Putri Ayu Kota Jambi - Alisia, Meli; Sari, Putri Irwanti; Yusnilawati, Yusnilawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this study was to determine the effect of PMR training on reducing blood pressure in hypertensive patients. This research uses a quantitative approach with a quasi-experimental design with a two group pretest-posttest design approach. The sampling method in this research was simple random sampling and a sample of 50 people was obtained. 25 respondents in the intervention group and 25 respondents in the control group. Bivariate analysis used the Wilcoxon test and the Man Whitney test. The results of the study showed that there was a significant effect between reducing blood pressure in hypertension sufferers before and after being given progressive muscle relaxation (PMR) in the working area of the Putri Ayu Community Health Center, Jambi City.